The wisdom of the bullfrog leadership made simple (but not easy) - McRaven, William H. (New York Grand Central Publishing, 2023)
From the acclaimed, #1 New York Times bestselling author of Make Your Bed, a short, inspirational book of advice and leadership lessons that Admiral McRaven collected over his four decades as a Navy SEAL"-
Keywords: Leadership